TRAINING NEEDS FOR PHYSICAL EDUCATION TEACHERS IN JORDAN IN LIGHT OF THE REQUIREMENTS OF THE KNOWLEDGE ECONOMY FROM THE POINT OF VIEW OF TEACHERS THEMSELVES - Lubna Mahmoud Obeidat,; Mohammad Omar Al-Momani,; Saa Saleh Obeidat, (Sport Scientific And Practical Aspects, 2026)
The study aimed to identify the training needs of physical education teachers in light of the requirements of the knowledge economy, from the perspective of physical education teachers in Jordan. The study used a descriptive approach, and a training needs questionnaire was used as a study tool. The questionnaire consisted of (23) items. The study sample consisted of (231) male and female teachers. The study results showed that the training needs of physical education teachers in light of the requirements of the knowledge economy, from the perspective of physical education teachers in Jordan, were (moderate), with an arithmetic mean of (2.98) and a standard deviation of (0.59). The study also found no statistically significant differences in training needs attributable to the variables of gender and number of years of experience.